ANTIMICROBIAL PEPTIDES — A POTENTIAL REPLACEMENT FOR TRADITIONAL ANTIBIOTICS - Kh. G. Musin (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
Antimicrobial peptides are a heterogeneous group of molecules involved in the innate and acquired immune response of various organisms, ranging from prokaryotes to mammals, including humans. They consist of 12–50 amino acid residues; have different physico-chemical and biological properties. The most common feature is their ability to destroy the prokaryotic cell membrane, which causes cell death. In the action, the molecules of antimicrobial peptides are embedded in the target bacteriological cells and change their conformation, forming structures in some cases resembling channels. Some other molecules of antimicrobial peptides can cover the surface of a bacteriological cell and form a carpet, when they reach a critical mass they act like detergents. In addition, being positively charged molecules of such peptides, penetrating through the membranes of parasitic and bacteriological cells, bind to polyanionic RNA and DNA molecules. Among the benefits of antimicrobial peptides is their high metabolic activity, low probability of occurrence of addictions and side effects. In addition, bacteriological pathogens that previously did not have resistance to any antimicrobial peptide are difficult to develop a strategy to control them. In this connection, these peptides are the most promising moleculessubstitutes for traditional antibiotics. The article discusses the approaches and strategies of therapeutic use, the studies of antimicrobial peptides identified in recent years; The most frequently encountered mechanisms of interaction of antimicrobial peptides and a bacteriological membrane are described, the physicochemical properties of peptide molecules are described; the results of studies on the detection of resistance of some strains of bacteria to antimicrobial peptides and antibiotics in general are summarized.